HUBUNGAN PENGETAHUAN TENTANG PROGRAM GEMAR BERTASBI (GERAKAN MASYARAKAT BRANTAS TB PARU) DENGAN TINDAKAN PENCEGAHAN TUBERKULOSIS PADA KADER TB PARU DI WILAYAH KERJA PUSKESMAS BANGSAL KABUPATEN MOJOKERTO - Linda Wahyudi; Henry Sudiyanto; Eka Diah Kartiningrum (MEDICA MAJAPAHIT, 2019)
Tuberculosis (TB) Lung is an old disease that is the most killer among infectious diseases. Lung tuberculosis prevention efforts made by the government through the GEMAR BERTASBI Program (Pulmonary TB Brantas Community Movement). This program is carried out by a cadre of puskesmas. This study uses a cross sectional approach, the number of respondents is 36 cadres of health centers according to the inclusion criteria, and given a number of questions using the GEMAR BERTASBI questionnaire to find out the level of cadre knowledge and the questionnaire tuberculosis prevention measures know positive or negative preventive actions taken at one time. The results obtained as many as 9 (52.9%) good knowledge and take positive precautions. 3 (25.0%) sufficient knowledge and take positive precautions, 1 (14.3%) lack knowledge and take positive precautions. Analysis of research data using the Spearman 's rho statistical test with the results of p value = 0.044 (p value <0.05) means that there is a relationship of knowledge about the GEMAR BERTASBI (Gerakan Masyarakat Brantas TB Paru) program with tuberculosis prevention measures. It is recommended that pulmonary TB cadres understand the GEMAR BERTASBI program and participate in tuberculosis prevention measures.